Healthcare utilisation and empowerment among women in Liberia. - Sipsma, Heather; Callands, Tamora A; Bradley, Elizabeth; Harris, Benjamin; Johnson, Billy; Hansen, Nathan B (Journal of epidemiology and community health, 2013)
Many efforts have been undertaken to improve access to healthcare services in low-income settings; nevertheless, underutilisation persists. Women's lack of empowerment may be a central reason for underutilisation, but empirical literature establishing this relationship is sparse.
Keywords: Cross-Sectional Studies; Female; Health Services; Health Services Accessibility; Health Surveys; Humans; Liberia; Logistic Models; Multivariate Analysis; Patient Acceptance of Health Care; Power (Psychology); Prevalence; Questionnaires; Socioeconomic Factors